MRI IMAGING FEATURES IN GLOBAL HYPOXIC ISCHEMIA - SUBHASH SINGLA MD; ANKUR WADHERA MBBS (International Journal of Pharma and Bio Sciences, 2013)
Hypoxic changes in brain can vary from mild focal ischemia/ infarction to severe global changes causing permanent neurological disability or death. It is important to recognise and describe the extent of these changes so that the treating physician and the relatives can take the best possible curative/palliative treatment decision for the patient. We present one such case showing global hypoxic ischemic changes in the brain in a patient following a cardiac arrest.